EFFECT OF COMPANY FINANCIAL RATIO, PRICE EARNING RATIO ON STOCK RETURN AND EARNING PER SHARE AS MODERATING VARIABLES IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Parapat, Eka Pratiwi Septania (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the study was to test and analyze the influence of Company’s   Financial Ratio and Price Earning Ratio simultaneously and partially on Stock Return with Earning Per Share as moderating variable in Manufacture Companies listed in IDX (Indonesia Stock Exchange). The data were gathered by using secondary data. The population was manufacture companies listed in IDX, and42 of them were used as the samples. The data were analyzed by using multiple linear regression analysis and residual regression analysis. The result of the study showed that the variables of Financial Ratio (Leverage, Liquidity, and Probability) and Price Earning Ratio simultaneously had significant influence on the variable of Stock Return, the variables of Leverage and Liquidity partially did not have any influence on Stock Return, and the variables of Profitability and Price Earning Ratio partially had significant influence on Stock Return in Manufacture Companies listed in IDX. The variable of Earning Per Share as moderating variable would be able to strengthen the correlation of Leverage, Liquidity, Profitability, and Price Earning Ratio with Stock Return in Manufacture Companies listed in IDX.